2020
DOI: 10.1536/ihj.20-058
|View full text |Cite
|
Sign up to set email alerts
|

Physical Function and Cardio-Ankle Vascular Index in Elderly Heart Failure Patients

Abstract: The number of heart failure patients is increasing rapidly in Japan because of its large elderly population. As age increases, arterial stiffness and physical dysfunction progress. This study aimed to evaluate the association between the physical function and arterial stiffness in elderly heart failure patients.This retrospective, observational study includes data from 100 heart failure patients aged !65 years who were admitted to our hospital and underwent cardiac rehabilitation. The Cardio-Ankle Vascular Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…There was weak association between CAVI and exercise capacity in the present study. Concordant with our data, it has recently been reported that CAVI was associated with 6min walk test, and indicated that arterial stiffness may relate to partly exercise capacity (17). Regarding arterial stiffness and impaired exercise capacity in HF patients, abnormal ventriculararterial coupling may be caused by vascular dysfunction in HF (4).…”
Section: Discussionsupporting
confidence: 91%
“…There was weak association between CAVI and exercise capacity in the present study. Concordant with our data, it has recently been reported that CAVI was associated with 6min walk test, and indicated that arterial stiffness may relate to partly exercise capacity (17). Regarding arterial stiffness and impaired exercise capacity in HF patients, abnormal ventriculararterial coupling may be caused by vascular dysfunction in HF (4).…”
Section: Discussionsupporting
confidence: 91%
“…CAVI, cardio-ankle vascular index; CV, cardiovascular; CAD, coronary artery disease; CVD, cardiovascular disease; NRI, net reclassification improvement; MI, myocardial infarction; HR, hazard ratio; ACS, acute coronary syndrome; OR, odds ratio; SD, standard deviation; MACE, major adverse cardiovascular events; GRACE, global registry for acute coronary events CAVI may also improve LV function and prevent heart failure. Recently, Ogawa et al 109) reported that CAVI and physical function assessed by 6-minute walk distance are complementary to each other in elderly heart failure patients. Development of new cardiac rehabilitation by monitoring CAVI is anticipated.…”
Section: 8mentioning
confidence: 99%
“…Since the LV function and morphology are closely related to arterial stiffness, treatments that improve CAVI may also improve LV function and prevent heart failure. Recently, Ogawa et al 109 ) reported that CAVI and physical function assessed by 6-minute walk distance are complementary to each other in elderly heart failure patients. Development of new cardiac rehabilitation by monitoring CAVI is anticipated.…”
Section: The Possible Role Of Cavi In Cardio-vascular Interactionmentioning
confidence: 99%
“…11) For assessing the reproducibility of 3D echo quantification of mitral leaflet size and coaptationzone areas, two independent observers performed 3D echocardiographic measurements, and one observer repeated the measurements subsequently in 10 cases. Cardio-ankle vascular index: CAVI was measured by the VS2000 system (Fukuda Denshi, Tokyo) for assessing atherosclerosis 18,19) at the discretion of the attending physician. The mean CAVI was calculated as the average of right and left CAVI.…”
Section: Study Subjectsmentioning
confidence: 99%
“…17) In a previous study, 11) we found that some atherosclerosis-related risk factors were associated with mitral leaflet size and coaptation. We hypothesized that the cardio-ankle vascular index (CAVI), which is widely used for assessing atherosclerosis comprehensively, 18,19) may be associated with MV leaflet size. The aim of this study was to determine the association between the MV leaflet and coaptation-zone areas and the degree of atherosclerosis as assessed by CAVI 18,19) or other clinical factors in patients with normal LV systolic function and size by real-time 3-dimensional echocardiography (RT3DE).…”
mentioning
confidence: 99%